Sustainable development of Depok Beach, Yogyakarta: System dynamics approach to waste management and maritime economy enhancement - Didi Nuryadin; Jamzani Sodik; Wahyu Dwi Artaningtyas; Indra Wahyu Pratama (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2024)
Depok Beach is a tourist destination in Yogyakarta which has experienced significant development as part of the South Coast National Tourism Strategic Area of Yogyakarta. However, waste management is still the main challenge faced. The objectives of this study is to build a sustainable model for Depok Beach, to estimate the behaviour of the management system, and develop a strategy to promote the maritime economy in the. System dynamics was used for modelling the management strategy. Data were collected through observation and in-depth interviews with related stakeholders. The results showed that Depok Beach will continue to attract more tourists until 2030, but a decrease in visitor numbers is expected to occur after that. It is due to a decrease in the attractiveness value of the beach. Meanwhile, a comprehensive and integrated approach of policy implementation scenarios is needed to yield significant results. The development of Depok Beach required a comprehensive, integrated policy approach.